Agricultural Land Redistribution and Land Administration in Sub-Saharan Africa: Case Studies of Recent Reforms - Byamugisha, FrankF.K. (World Bank, 2015)
Agricultural Land Redistribution and Land Administration in Sub-Saharan Africa: Case Studies of Recent Reforms focuses on ?how? to undertake land reforms in Sub-Saharan Africa, but with relevant lessons for other developing countries. It provides details, with case studies, on how reforms were undertaken to address a pressing and controversial development challenge in Africa ? land ownership inequality ? and an intransigent development issue ? inefficiency and corruption in land administration. An equally important contribution of the book is assessing reforms and highlighting valuable lessons for other countries contemplating reforms.